Kesalahan Umum (Human Error) Dalam Perhitungan Volume Pekerjaan Dinding Dan Pengaruhnya Terhadap Pembengkakan Rab Studi Kasus: Gedung Politeknik Dewantara - Herlina Herlina; Anggel Erpa Erong Pakiding (CV. SINAR HOWUHOWU, 2026)
Precision in calculating construction work volumes is a critical aspect of preparing a Bill of Quantities (BoQ) and Cost Budget Plan (RAB) to prevent budget overruns and material shortages on site. This study aims to identify common estimator human errors and quantitatively analyze their impacts on material quantity deviations and cost overruns in the wall construction of the Dewantara Polytechnic Building in Palopo City. The research method employs a descriptive quantitative analysis comparing manual estimator calculations with corrected technical calculations based on AHSP 2026 standards (SE Dirjen Bina Konstruksi No. 47/SE/Dk/2026). Primary data were obtained from local material market price surveys in Palopo City in 2026, while secondary data included Detail Engineering Design (DED) drawings and AHSP 2026 guidelines. Quantitative results indicate that dominant human errors include failure to deduct frame opening areas, neglecting material waste factors, and inaccuracy in converting loose to compacted sand volume. In a sample classroom area of 70.00 m², the failure to deduct an opening area of 8.04 m² triggered a wall area overestimation of 12.98%. Consequently, this led to a budget overestimation for light brick procurement by 7.60% and Portland cement by 7.62%. Conversely, ignoring the sand volume conversion factor caused a sand requirement underestimation of 10.68%, posing a risk of halting construction operations due to material shortages. Overall, these accumulated human errors caused a total budget overrun of 5.90% to 7.28% for wall materials compared to actual requirements. Correcting calculations based on AHSP 2026 technical guidelines and adopting Building Information Modeling (BIM) technology effectively eliminate these discrepancies and enhance project cost estimation efficiency.